2005
DOI: 10.3354/meps299033
|View full text |Cite
|
Sign up to set email alerts
|

Columbia River plume fronts. II. Distribution, abundance, and feeding ecology of juvenile salmon

Abstract: Well-defined fronts develop at the seaward edge of riverine plumes where suspended materials and planktonic organisms are concentrated by convergent water flows. Riverine plume fronts have been hypothesized to be favorable fish habitats because they can lead to localized prey aggregations. We examined the spatial distribution of juvenile Pacific salmonids Oncorhynchus spp. in and around plankton-rich frontal regions of the Columbia River plume to test the hypothesis that juvenile salmonids aggregate at riverin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 34 publications
1
47
0
Order By: Relevance
“…Although a limited number of studies reflect on potential implications of a complete lack of river outflows on marine environments, it is generally understood that changing the scale, frequency and seasonality of river outflows can have severe impacts on species that require food pulses for successful reproduction or larval survival (Drinkwater and Frank 1994;Whitfield and Marais 1999). Several studies have identified important relationships between outflow-stimulated productivity and populations of marine species and habitats as a result of these controls (Burrage et al 2002;De Robertis et al 2005;Burla et al 2010;Brookes et al 2015;Black et al 2016). There is also a critical period at the point of first feeding by larvae where the presence of suitable amounts and types of food determine year-class strength (Hjort 1914).…”
Section: Discussionmentioning
confidence: 99%
“…Although a limited number of studies reflect on potential implications of a complete lack of river outflows on marine environments, it is generally understood that changing the scale, frequency and seasonality of river outflows can have severe impacts on species that require food pulses for successful reproduction or larval survival (Drinkwater and Frank 1994;Whitfield and Marais 1999). Several studies have identified important relationships between outflow-stimulated productivity and populations of marine species and habitats as a result of these controls (Burrage et al 2002;De Robertis et al 2005;Burla et al 2010;Brookes et al 2015;Black et al 2016). There is also a critical period at the point of first feeding by larvae where the presence of suitable amounts and types of food determine year-class strength (Hjort 1914).…”
Section: Discussionmentioning
confidence: 99%
“…During 12 days of surface trawling in May of 2001 and 2002, densities of juvenile yearling coho salmon, yearling Chinook salmon, and steelhead were generally higher in the plume compared to more marine waters, reflecting the outmigration of large numbers of juvenile salmon from the Columbia River estuary into coastal waters during this time (De Robertis et al 2005). Chum salmon were rare in the plume, possibly because Columbia River chum salmon populations were at low levels during the time of this study (De Robertis et al 2005).…”
Section: Use Of the Columbia River Plume By Juvenile Anadromous Salmomentioning
confidence: 81%
“…Many Columbia River salmonids, such as yearling coho salmon, yearling Chinook salmon, chum salmon, and steelhead, enter the ocean during late spring and early summer when river flows are high and the low-salinity plume is well developed (De Robertis et al 2005). During 12 days of surface trawling in May of 2001 and 2002, densities of juvenile yearling coho salmon, yearling Chinook salmon, and steelhead were generally higher in the plume compared to more marine waters, reflecting the outmigration of large numbers of juvenile salmon from the Columbia River estuary into coastal waters during this time (De Robertis et al 2005).…”
Section: Use Of the Columbia River Plume By Juvenile Anadromous Salmomentioning
confidence: 99%
See 2 more Smart Citations